ANALISIS POTENSI PENERIMAAN PAJAK HOTEL DI KOTA TOMOHON - Rawung, Megha Cicilia; Karamoy, Herman; Elim, Inggriani (Universitas Sam Ratulangi, 2015)
Regional Income is a source of regional finance and government financing. One of the original income receipts derived from the Regional Tax one of which is tax Hotel. This study was conducted to determine the potential of the hotel tax, the level of effectiveness and Contributions Taxes as a source of regional revenue Tomohon. The analysis method used is descriptive method Quantitative and analyze tax receipts Hotel of the Year 2011-2014. The results showed that the level of effectiveness of a Hotel Tax Year 2011-2014 ineffective. Taxes contribution as a source of regional revenue Tomohon over the last four years and a maximum rated not included in the criteria for contributions